MO753RELATIONSHIP BETWEEN MINERAL BONE DISEASE AND ATHEROSCLEROSIS IN NON-DIABETIC PERITONEAL DIALYSIS PATIENTS. (29th May 2021) - Andronesi, Andreea Gabriella; Iliuta, Luminita; Cristache, Cristina; Burcea, Andreea-Florentina; Lupusoru, Gabriela Elena; Obrisca, Bogdan; Andronesi, Danut; Lupusoru, Mircea; Sorohan, Bogdan Marian; Ismail, Gener
Abstract: Background and Aims: The term chronic kidney disease-mineral bone disorder has the role of highlighting that the disturbed mineral and bone metabolism is a major contributor to vascular calcification and finally cardiovascular disease in chronic kidney disease (CKD), especially in hemodialysis. This relationship was less studied in peritoneal dialysis (PD). The aim of the present study was to evaluate the impact of metabolic bone disorder (MBD) on symptomatic atherosclerosis (stable angina SA, acute coronary syndrome ACS, ischemic stroke, peripheral artery disease PAD) in non-diabetic PD patients. We choose to exclude diabetic patients since they are already at increased risk for atherosclerosis. Method: We performed a prospective study in non-diabetic population of patients in stable PD programme for at least 6 months. We analysed clinical and biological parameters of calcium-phosphate metabolism (calcemia Ca, phosphatemia P, CaxP product, intact parathormone iPTH), presence of atherosclerotic disease and we performed carotid ultrasound for measurement of intima media thickness (IMT) as a marker for subclinic atherosclerosis. Independent risk factors for atherosclerotic disease were identified by multivariate analysis through logistic regression using IBM SPSS ver. 20.0. Results: 246 consecutive non-diabetic PD patients (pts) were included (128M, 118F), mean age 56.3 + 15.7 years (20-85), with a follow up of 6.5±1.1 years. 19 pts (7.7%) had calcemia (Ca)>10.2 mg/dl, no patient had a Ca<8.2 mg/dl, 127 pts (51.6%) had phosphatemia (P)>5.5 mg/dl, 45 pts (18.3%) had CaxtaP product>55 mg2/dl2, 68 pts (27.6%) had iPTH<150 pg/ml, 95 pts (38.6%) had iPTH>300 pg/ml. We found a weak positive correlation between IMT and Ca (r=0.283, p=0.005); pts with iPTH<150 pg/ml and those with iPTH>300 pg/ml had a higher risk of increased IMT compared to pts with iPTH 150-300 pg/ml (OR 4.1, p=0.009, for iPTH<150 pg/ml, respectively OR 3.4, p=0.01 for iPTH>300 pg/ml). Pts with atherosclerotic disease had significantly higher P and CaxP, without differences regarding Ca and iPTH (Table 1 ). An iPTH<150 pg/ml was a risk factor for SA, ACS and PAD, while iPTH>300 pg/ml was a risk factor for SA and ACS (Table 2 ). We perfomed multivariate analysis to identify independent risk factors for SA, ACS, stroke and PAD by entering in the analysis the factors identified in univariate analysis to be significantly associated with different manifestations of atherosclerosis. Among independent risk factors identified for atherosclerotic disease, iPTH<150 pg/ml was risk factor for SA (adjusted OR 11.5, p=0.007) and ACS (adjusted OR 221.4, p=0.01), iPTH>300 pg/ml was risk factor for ACS (adjusted OR 5.2, p=0.03), CaxP >55 mg2/dl2 was risk factor for ACS (adjusted OR 33.5, p=0.02) and ischemic stroke (adjusted OR 4.4, p=0.01). No parameters of calcium-phosphate metabolism were identified as independent risk factors for PAD. Conclusion: We found significant independent correlations between different parameters which characterize MBD and presence of symptomatic atherosclerosis in non-diabetic PD pts. The most important risk factors identified were abnormally low or high iPTH level, and elevated CaxP. The most striking result was the low iPTH associated with SA and especially ACS, suggesting that an adynamic bone is incapable to buffer the serum calcium and phosphate, thus increasing the risk of vascular calcifications. Future studies may address the issue whether correction of these parameters may be associated with attenuation of atherosclerotic disease in this population.